Scientific publications on education during the COVID-19 pandemic and International education policy guidelines - Gómez Velasco, Nubia Yaneth; Lima Jardilino, José Rubens; Pedraza Díaz, Diana Marcela (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: The purpose of this article is to analyze the research trends on education during the pandemic and their connection with the guidelines of international organizations aimed at solving the crisis in the educational environment during 2020. Originality/support: This work identifies the lines of interest that emerged in educational research as a consequence of covid-19 during 2020 and its influence, if any, in the generation of international policies and in Latin America. Method: A study of scientific publications on the topic "education in covid-19 pandemic" in two international databases, Web of Science and Dialnet. The former containing data from American and European publications and the latter with data from Latin America and the Caribbean. The documentary search is complemented by guidelines and directives on educational policies issued by international organizations, such as UNESCO, UNICEF, among others. The methodology used here follows a mixed approach. Strategies/information collection: by using bibliometric techniques with the metadata of the 2020 publications and relying on documentary analysis from a semiotic perspective, Conclusions: it was found that the publications in WoS essentially focus on concerns about students, education and technologies, while the publications on Dialnet focus on questions and reflections on the effect of covid-19 on students from a social and educational perspective. This shows two defining lines, an international one related to educational tools and a regional one centered on the student as a being in the process of formation.